TMEM138: From Biological Functions to Diseases. - Qinghan SHI; Lingling ZHU; Lan ZHANG; Zhaolun GUO; Yafei HAO; Yongmei WANG; Jiangang GAO; Hua LI; Min LIU (Physiological Research, 2025)
Transmembrane Protein 138 (TMEM138) is a transmembrane protein belonging to the superfamily of transmembrane proteins. Recent research has unveiled its involvement in various biological processes such as cell proliferation, differentiation, and apoptosis. Furthermore, abnormal expression of TMEM138 has been linked to a range of diseases, particularly neurodegenerative diseases and tumors. This review provides an overview of TMEM138, focusing on its molecular characteristics, biological functions, and potential roles in disease pathogenesis. The aim is to offer a valuable reference for future research and clinical applications.